Kritik Sosial dalam Lirik Lagu Konsekuens oleh Grup Musik .Feast: Kajian Semiotika - Muhammad Asyari; Dwi Wahyu Candra DewI (STIKes Ibnu Sina Ajibarang, 2025)
This writing is motivated by the author's endeavor to understand the meaning within song lyrics. From this meaning, the myths and messages that the songwriter attempts to convey can also be discerned. This research employs a qualitative descriptive method. The data sources obtained are from secondary data and public data sources. In this study, the connotative and denotative meanings in the song 'Konsekuens' by the music group .Feast can be understood by the author, thus enabling the identification of social criticism present in the lyrics of this